Выражение: -8)^2-2(х+8)(х-3)+(-х+3)^2 б)3(3а-1)^2-2(-4а-2)^2+5 15б

Vceohenploxo Vceohenploxo    2   08.09.2019 13:50    0

Ответы
Sofia1234567891 Sofia1234567891  01.09.2020 10:20
.....................................
Выражение: -8)^2-2(х+8)(х-3)+(-х+3)^2 б)3(3а-1)^2-2(-4а-2)^2+5 15б
ПОКАЗАТЬ ОТВЕТЫ
sadpoli sadpoli  01.09.2020 10:20
А) (-х-8)^2-2(х+8)(х-3)+(-х+3)^2
    х^2+16x+64-2(x^2-3x+8x-24)+x^2-6x+9
    x^2+16x+64-2x^2+6x-16x+48+x^2-6x-9
    сократятся все х^2 и х,останется: 103
б)3(9а^2-6a+1)-2(16a^2+16a+4)+5
    27a^2-18a+3-32a^2-32a-8+5
    -5a^2-50a=0, делим всё на -5
    a^2+10а=0
    а(а+10)=0
    а=0 или а=-10
Надеюсь что правильно)
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра